2016
DOI: 10.1007/s00168-016-0768-3
|View full text |Cite
|
Sign up to set email alerts
|

Industrial scope of agglomeration economies in Brazil

Abstract: The tendency towards urbanization in the emerging world accompanied by the constant pursuit for higher productivity prompts an urge for studies aiming at understanding agglomeration economies. In the context of Brazil, a country with extremely high regional disparities, exploring this issue is important not only for private stakeholders, but also for public policy practitioners. In the framework of static agglomeration effects, we investigate the industrial scope of agglomeration economies in Brazil. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 38 publications
7
41
1
1
Order By: Relevance
“…Beaudry and Schiffauerova () emphasize that, in most cases, the models result in negative or non–significant effects of specialization externalities. For the Brazilian economy, Catela et al () and Barufi et al () also identified a positive effect for Brazil. Graham (), Kemeny and Storper () and Caragliu et al () found a positive effect of specialization on local growth for Great Britain, the United States and European regions, while Mameli et al () identified positive effects of specialization for industry at three‐digits of aggregation for Italy, although it found a negative effect at two‐digits.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Beaudry and Schiffauerova () emphasize that, in most cases, the models result in negative or non–significant effects of specialization externalities. For the Brazilian economy, Catela et al () and Barufi et al () also identified a positive effect for Brazil. Graham (), Kemeny and Storper () and Caragliu et al () found a positive effect of specialization on local growth for Great Britain, the United States and European regions, while Mameli et al () identified positive effects of specialization for industry at three‐digits of aggregation for Italy, although it found a negative effect at two‐digits.…”
Section: Resultsmentioning
confidence: 93%
“…Robust standard errors in parentheses. Barufi et al (2016). However, Mameli et al (2014) found a negative result for two-digit and a positive one for three-digit aggregation level.…”
Section: Figurementioning
confidence: 89%
See 1 more Smart Citation
“…Most of the previous studies showed positive effects for Brazilian regions concerning diversification (Badia & Figueiredo, ; Silva & Silveira Neto, ; Fochezatto & Valentini, ; Catela et al, ). Barufi et al () found this for high technological sectors, while Araújo et al () sees positive effects from diversification from neighbouring regions. What can be seen here is that in fact the positive effects from diversification emanate when sectors are diversified, but related with each other.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, the hypothesis of a region's economic performance depending on the ones around it is considered. These spatial externalities were also controlled by Dauth (2013) and Barufi et al (2016). We use the spatial lag of the X (SLX) model as it is the most flexible among all other spatial models because it is easily interpretable in terms of signal, magnitude and significance level (Vega & Elhorst, 2015).…”
Section: Model Identification Strategymentioning
confidence: 99%